Jobs and Growth : Supporting the European Recovery: Supporting the European Recovery - Schindler, Martin (International Monetary Fund, 2014)
Five years after the onset of the global financial crisis, Europe's economy is still fragile. Notwithstanding recent positive signs amid calmer financial markets, medium-term growth is likely to remain frail owing to continuing weaknesses and vulnerabilities at the country level and in the fabric of European institutions and banks, especially in the euro area. In addition, unemployment in many countries has reached very high levels. The IMF research collected in this volume provides a number of guideposts that offer an opportunity for stronger and better-balanced growth and employment in Europe after what has been a long and dismal period of crisis.